TINGKAT ADOPSI PETANI TERHADAP PENGGUNAAN BENIH BERSERTIFIKAT PADA AGRIBISNIS PADI ADOPTION OF FARMERS TO USE THE SEED CERTIFIED IN RICE AGRIBUSINESS - Sri Ayu Andayani (REPOSITORY BUKU DAN JURNAL)
Developments in the production of rice agribusiness has a tendency to decline interms of effectiveness and efficiency, it is characterized by decreased efficiency of theprovision of inputs, decreasing rate of increase in crop yield and frequent pest. Thiscondition also occurred in the village of Wanasaba Kidul and Kubang District of TalunCirebon, West Java, productivity achieved not in accordance with what is expected, onereason is the farmers are not fully implement a package of farming technology inaccordance with the recommended, especially in the use of improved seed certified ,Seeing this, the research is needed to see the adoption rate of farmers against the use ofimproved seed certified and comparison of income between rice farming that is alreadyusing certified seed and which have not implemented. The results showed that therewere differences in income between agribusiness rice using certified rice seeds with nouse. The adoption rate of farmers on the use of improved seed certified in WanasabaKidul village categorized quite good, while the adoption rate of certified rice seeds tofarmers in the village of Kubang District of Talun including unfavorable category. Theadoption rate of farmers on the use of so-yielding rice seeds certified in additioninfluenced by the characteristics of the farmers themselves, namely: level of education,experience farming, land and farm income is also influenced by the five other factors: a.gain added value relative if the technology is adopted, b match technology with localculture, c observations of farmers to other farmers who have tried and tried himself tobe successful technologies, d try for themselves the success of new technology and e theexisting economic conditions such as the availability of capital ,Keywords: Adoption level, superior certified seed, rice agribusiness